Improvement of physiological and phytochemical parameters of pot marigold (Calendula officinalis) using foliar application of zinc - Zahra Sobati-Nasab,; Abolfazl Alirezalu,; Parviz Noruzi, (Agriculture and Natural Resources, 2021)
The foliar application of micronutrients directly affects quality and yield. A pot experiment was used to investigate the effect of different concentrations of zinc (Zn) on the physiological and phytochemical traits of marigold (Calendula officinalis). Treatments consisted of five different concentrations of zinc nitrate (0 mg/L as the control; 0.5 mg/L; 1 mg/L; 1.5 mg/L; 2 mg/L) in four replications. The foliar application of the different concentrations of Zn was performed in two stages, with the first stage at 2–4 leaves and the second stage at the time of budding. The results indicated that different concentrations of Zn significantly affected the physiological and phytochemical parameters of marigold. The best Zn concentration for fresh weight traits, chlorophyll index, chlorophyll a, chlorophyll b, total carotenoid and β-carotene, was the fourth treatment (1.5 mg/L) of Zn. However, for the lycopene, anthocyanin, total phenol and total flavonoid traits, the highest measured value was related to the fifth treatment (2 mg/L). Finally, the best antioxidant activity in both assays applied was observed in the third treatment (1 mg/L). Therefore, application of appropriate concentrations of Zn can improve the physiological and phytochemical traits of pot marigold flowers.